Synthesis and Antimicrobial Activities of Some Transition Metal Benzimidazole Complexes - Kucukbay, Hasan; Gunal, Selami; Orhan, Ersin; Durmaz, Riza (Asian Journal of Chemistry, 2010)
The interaction of N-monosubstituted benzimidazoles with various metal salts [CoCl 2, NiCl2 and Zn(OAc)2)] were yielded stable solid metal benzimidazole complexes. All the metal complexes were identified by 1H NMR, FT-IR spectroscopic techniques, elemental analysis and screened for their in vitro antimicrobial activities against the standard strains: Enterococcus faecalis (ATCC 29212), Staphylococcus aureus (ATCC 29213), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853) and yeasts Candida albicans and Candida tropicalis. Some of the compounds inhibited the growth of gram-positive bacteria (E. faecalis and S. aureus) at MIC values between 200 and 800 μg/mL. None of the compounds exhibit antimicrobial activity against gram-negative bacteria (mL). Some of the tested compounds exhibit an antifungal activity with a range of the MICs between 100 and 800 μg/mL.